2010
DOI: 10.1080/15598608.2010.10411981
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Polygonal Designs with Block Size 3 and λ = 1 for Joint Distance α = 6 to 16

Abstract: Stufken (1993) first introduced cyclic polygonal designs (CPDs) (in terms of cyclic balanced sampling plans excluding adjacent units (CBSAs)) for joint distance α ≥ 2. Wei (2002) first suggested the use of Langford sequence for the existence and construction of CPDs with block size k = 3 and λ = 1 for arbitrary α. Zhang and Chang (2005b) used Langford and extended Langford sequence, and constructed CPDs (in terms of CBSAs) with block size k = 3 and λ = 1 for joint distance α = 2, 3. Zhang and Chang (2006) also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…. , 16, the existence of circular BSAs were completely determined if the BSAs have a full cyclic automorphism group [25,31,33] (the so called Cyclic Polygonal Designs or cyclic BSA). The case when k = 4 was considered in [34].…”
Section: Preliminarymentioning
confidence: 99%
“…. , 16, the existence of circular BSAs were completely determined if the BSAs have a full cyclic automorphism group [25,31,33] (the so called Cyclic Polygonal Designs or cyclic BSA). The case when k = 4 was considered in [34].…”
Section: Preliminarymentioning
confidence: 99%
“…Colbourn and Ling (1998, 1999) and Tahir et al (2010Tahir et al ( , 2012 suggested some techniques to obtain BSA plans with the assumption that the population have a circular ordering. They constructed all the polygonal designs for 𝜈 ≤ 100, 𝑘 = 3 for all permissible 𝑚 using the approach.…”
Section: Balanced Sampling Plan Excluding Adjacent Units (Bsa Plan)mentioning
confidence: 99%